2016
DOI: 10.1039/c5fo01094b
|View full text |Cite
|
Sign up to set email alerts
|

Gracilaria edulis exhibit antiproliferative activity against human lung adenocarcinoma cell line A549 without causing adverse toxic effect in vitro and in vivo

Abstract: In the present study, the antiproliferative potential of various solvent extracts of Gracilaria edulis (GE) was tested against various cancer cell lines. In the A549 lung cancer cell line model, GE ethyl acetate extract (GEEA) (100 μg mL(-1)) treated group showed the maximum and significant (P < 0.05) growth inhibition at 48 h. The IC50 value was found to be 24.5 ± 19.1 μg mL(-1) at 48 h. Moreover, a low level of LDH release was observed at 48 h at various concentrations of (40, 60, 80 and 100 μg mL(-1)) GEEA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Natural sources such as plants, microorganisms and marine organisms are potential bioresources for anticancer compounds 5 . Earlier studies reported that the seaweeds Undaria pinnatifida , 6 Gracilaria edulis , 7 Turbinaria conoides , 8 and Sargassum pallidum 9 exhibit anti-proliferative effects against human lung cancer cells (A549).…”
Section: Introductionmentioning
confidence: 99%
“…Natural sources such as plants, microorganisms and marine organisms are potential bioresources for anticancer compounds 5 . Earlier studies reported that the seaweeds Undaria pinnatifida , 6 Gracilaria edulis , 7 Turbinaria conoides , 8 and Sargassum pallidum 9 exhibit anti-proliferative effects against human lung cancer cells (A549).…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that prophylactic administration of fucoidans suppress lung cancer metastasis by inhibiting MMPs and VEGF [57]. Besides that, fucoidans have the ability to present a synergistic effect towards the anticancer agents currently in use [41]. This has emphasized the need for further research by combining such polysaccharides with the existing medicines to improve the efficacy of conventional drugs.…”
Section: Fucoidanmentioning
confidence: 99%
“…Phycocyanin which is a blue colored phycobiliprotein produced essentially from Arthrospira sp., reportedly showed anticancer properties against A549 lung cancer cells [30]. Previous study mentioned the use of phycocyanin individually and/or in combination with other agents to obtain anticancer effects against lung cancer [40,41]. Phycoerythrin (pink colored protein pigment) produced by a marine Lyngbya showed apoptotic activity against A549 human lung carcinoma cells [64].…”
Section: Phycobiliproteinmentioning
confidence: 99%
“…The polyunsaturated esters in G. edulis showed antibacterial activity against several human pathogens. G. edulis extracts can inhibit carcinoma cell activity (Sakthivel et al 2016). To date, studies have mainly focused on the identification of antitumor active compounds in G. edulis (Patra and Muthuraman 2013).…”
mentioning
confidence: 99%